Influence of combined transcranial and peripheral electromagnetic stimulation on the autonomous nerve system on delayed onset muscle soreness in young athletes: a randomized clinical trial - Hugo Keriven; Alberto Sánchez Sierra; Ángel González-de-la-Flor; María García Arrabé; Marta de la Plaza San Frutos; Arturo Ladriñán Maestro; Guillermo-Garcia-Perez-de-Sevilla; Jose Francisco Tornero Aguilera; Vicente Javier Clemente Suarez; Diego Domínguez Balmaseda (Journal of Translational Medicine)
Abstract Background Delayed Onset Muscle Soreness (DOMS) represents a common challenge for athletes and has been a focal point of research in sports science. Eccentric exercise, known to induce DOMS, significantly impacts recovery and physiological processes. Electromagnetic stimulation, both transcranial and peripheral, has gained attention in sports medicine due to its demonstrated benefits in various conditions, offering potential as a recovery-enhancing tool for athletes. Purpose This study aimed to evaluate the effects of combined transcranial and peripheral electromagnetic stimulation on the autonomic nervous system response and recovery in young athletes experiencing DOMS. Methods A randomized, double-blind study was conducted with 48 young athletes divided into four groups: Control (n = 12), Peripheral Stimulation (n = 13), Transcranial Stimulation (n = 11), and Combined Stimulation (n = 12). Participants underwent an eccentric exercise session to induce DOMS, followed by their respective interventions: no stimulation for the Control group, 5 min of peripheral electromagnetic stimulation (LTP protocol) for the Peripheral group, 20 min of transcranial stimulation for the Transcranial group, and a combination of both (30 min total) for the Combined group. The autonomic nervous system was assessed through Heart Rate Variability (HRV) parameters measured before, immediately after, and at 24 h, 48 h, and 72 h post-intervention. Results The Combined Stimulation group exhibited significant improvements in HRV parameters, including increased Low Frequency (LF, p < 0.001), High Frequency (HF, p < 0.001), and LF/HF power ratio (p < 0.001) at 72 h post-intervention compared to other groups. These findings suggest that paired-associative electromagnetic stimulation effectively enhances autonomic regulation and promotes recovery after eccentric exercise-induced DOMS. Conclusions Combined transcranial and peripheral electromagnetic stimulation positively influences autonomic nervous system responses, accelerating recovery in young athletes without disrupting natural physiological recovery mechanisms. This approach presents a promising recovery intervention for athletes experiencing DOMS.